Effects of black sand on Oreochromis niloticus: insights into the biogeochemical impacts through an experimental study - Saad, Eman; Sayed, Alaa El-Din H. (Frontiers in Earth Science, 2023)
Rare earth metals, thorium, titanium, tungsten, and zirconium are found in black sand (BS) after weathering and corrosion. Precious metals are not the only valuable elements in black sand, rare earth elements, thorium, titanium, tungsten, and zirconium are also found. The aquatic life in lakes and reservoirs is negatively affected by lithophilic elements such as lithium, uranium, and tin. Accordingly, intensive experiments were conducted on Nile tilapia (Oreochromis niloticus) after exposure to isolated black. Blood biomarkers, antioxidant balance, morpho-nuclear erythrocyte's alterations, and histopathological signs have been investigated after fish exposure for 15 days to 6.4 g BS /kg diet, 9.6 g BS /kg diet, and 2.4 g BS /kg diet. The blood profile, including platelets and white blood cells, has been pronouncedly decreased as a result. Functions of the liver and kidneys were impaired. An increase in serum-antioxidant enzymes as catalase activities and superoxide dismutase was recorded. Also, exposure to black sand induced cellular and nuclear abnormalities in the erythrocytes. In conclusion, the black sand isolated from the Red sea beach influenced Oreochromis niloticus's hematology, biochemistry, and antioxidant parameters. Poikilocytosis and RBC nuclear abnormalities were also associated with exposure to black sand. The resulting erosion of rocks and rocks' access to water forces us to consider the seriousness of climatic change on the aquatic ecosystem.